2017
DOI: 10.22159/ajpcr.2017.v10i11.20741
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Content and Free Radical Scavenging Activity of Representative Medicinal Plants of Thailand

Abstract: Objective: Plants are the vital source of pharmaceutically important compounds with less or no adverse side effects. The current study was conducted to catalog the commonly used indigenous and medicinal plants of Thailand based on their phenolic acid content and antioxidant activity. Methods:The herbs were collected from Chiang Mai province, Thailand. The plants were extracted with 70% ethanol. The total phenolic acid content and antioxidant activity were evaluated. Results:The ethanolic extract of plant sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The literature survey reported that the leaves of G. inodorum had many phytochemical compounds such as phenolics, flavonoids, terpenoids, and glycoside [13,14]. Moreover, its antioxidant, antiadipogenesis, antidiabetic, and hypoglycemic effects were also reported [14][15][16]. Therefore, the phytochemical constituents presented in G. inodorum may contribute to its biological activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature survey reported that the leaves of G. inodorum had many phytochemical compounds such as phenolics, flavonoids, terpenoids, and glycoside [13,14]. Moreover, its antioxidant, antiadipogenesis, antidiabetic, and hypoglycemic effects were also reported [14][15][16]. Therefore, the phytochemical constituents presented in G. inodorum may contribute to its biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the phytochemical constituents presented in G. inodorum may contribute to its biological activity. Numerous studies exhibited that the phytochemical compounds, especially flavonoids and phenolic content, had contributed to the redox-modulating properties of natural compounds, which had also been shown to modulate the inflammatory response virtually [15][16][17]. Along this line, it is possible that G. inodorum may exert a beneficial effect on alleviating intracellular ROS and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The total phenolic content of the samples was determined by the modified Folin-Ciocalteu colorimetric method as described previously [26,27]. The absorbance was measured at 725 nm after 30 min incubation at room temperature (RT).…”
Section: Determination Of Total Polyphenolic Contentmentioning
confidence: 99%
“…The TPC of the coffee extracts was determined by Folin-Ciocalteu colorimetric method as prescribed previously [10], and TPC was denoted as mg of gallic acid equivalent (GAE) per g of sample.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%